The Struggle for Job Ownership in the Canadian Steel Industry: An Historical Analysis - Storey, Robert (Labour/Le Travailleur, 1994)
This paper centres on the struggles over job ownership between labour and management that have been integral to the shaping and reshaping of the Canadian steel industry over the course of the 20th century. In the first phase of industry development (1900-1940s), management had virtual control over the structuring of jobs. The second phase (1940s-1970s) saw the arrival of industrial unionism and the establishment of seniority and grievance systems which gave workers employment security and, over time, a sense of job ownership. The third phase (1980s) has been a period of crisis in which steel management in Canada has embarked on a restructuring campaign — a critical feature of which is their determination to recapture job ownership through the introduction of new technologies, job amalgamations, and the implementation of teams. If steel management succeeds in wresting job ownership back from its workers, the paper concludes, then conditions will return to the pre-union period where management created and destroyed jobs as they desired.